Probiotics And Prebiotics As Feed Additive For Nonruminants - Tuti Haryati (Indonesian Center for Animal Research and Development, 2011)
The ban against using antibiotics has led to increase the use of alternative additive substances as antibiotic. The alternative additives that can be used as antibiotic are probiotic and prebiotic. Both components can be used separately or together as synbiotic. Probiotic and prebiotic can modulate the ecosytem of intestinal microflora that is potential to affect the health and performance of host. Probiotic and prebiotic have been widely used abroad because of their positive effects, but the research and the use of these components in Indonesia are limited, eventhough abundance of raw material that can be used are available. The research dealing with probiotic and prebiotic as additive is necessary to be improved to obtain the efficient and practical production method, which can be implemented to give an economic impact on livestock industry. Key words: Probiotic, prebiotic, additive, livestock